Serum vitamin A and subsequent risk of cancer: cancer incidence follow-up of the Finnish Mobile Clinic Health Examination Survey. - Knekt, P; Aromaa, A; Maatela, J; Aaran, R; Nikkari, T; Hakama, M; Hakulinen, T; Peto, R; Teppo, L (1990)
From 1968 to 1977, the association between the level of vitamin A in serum and the subsequent incidence of cancer was examined in a longitudinal study of 36,265 persons initially aged 15-99 years in 25 population groups in Finland. During a mean follow-up of 8 years, 766 cancers were diagnosed. Serum retinol, retinol-binding protein, and beta-carotene levels were measured from frozen serum samples (stored at -20 degrees C) drawn from these persons before the start of follow-up and from 1,419 controls matched for sex, age, and place of residence who did not develop cancer during follow-up. The mean level of serum retinol among the cancer cases was 645 micrograms/liter for men and 587 micrograms/liter for women. The corresponding levels in the controls were 3.3% and 2.8% higher. There was an inverse gradient between serum retinol level and the occurrence of cancer among men. This association was, however, mainly concentrated in the first 2 years of follow-up. The mean level of serum beta-carotene was 72.3 micrograms/liter among male cases and 119.5 micrograms/liter among female cases. The corresponding levels of the controls were 14.0% and 5.5% higher. The differences were particularly clear with regard to lung cancer. These findings suggest that the association between retinol and cancer may be due to preclinical cancer and that there may be an association between beta-carotene and cancer.